Three-dimensional analysis of posed smile in adults: A scoping review - Patcharamas Banditsaowapak; Johnson Hsin-Chung Cheng; Daniel De-Shing Chen; Michelle Yuching Chou (Elsevier, 2024)
This scoping review investigated the evidence on the three-dimensional analysis of a posed smile in adults to discover any research gaps in this research area. Electronic searches of articles written in English were performed using the four databases of Embase, PubMed, Springer, and Web of Science with publications from 2010 to 2023. Reference lists were also manually searched to identify additional studies. The results showed that 13 cross-sectional descriptive studies from Asia, Europe, North and South America met our inclusion criteria. Studies mainly focused on linear and angle measurement for resting and smiling faces and landmark movement from resting to smiling. Most studies conducted analysis of smiles stratified by sex, ethnicity, smile type, dental occlusion, skeletal pattern, and age. Two studies compared smiling with the resting position and one study compared the attractive smiling group with the ordinary group. Our scoping review revealed the insufficiency of some measurement methods, such as those employing area, volume, and soft tissue thickness. Furthermore, few studies were conducted in Asian populations, and comparisons of various smile types, overjet types, horizontal skeletal patterns, and comparisons of smiles between people with untreated normal occlusion and those who had been orthodontically treated were lacking.